Gambaran Stereotype Gender di Wilayah Kabupaten Jember - Sriwijayanti, Siska; Widyarini , Nurlaela; Linsiyah , Ria Wiyatfi (Indonesian Journal Publisher, 2024)
The discussion about gender Stereotypes is something complex that occurs among the general public. Gender Stereotypes will greatly influence a person's perception and even behavior towards a particular gender. The focus of this research is to examine more deeply the depiction of gender Stereotypes that exist and develop in society, especially in the Jember Regency area. The number of research participants was 160 respondents aged 18 - 68 years, male and female, with a minimum education equivalent to high school. The research method used is a descriptive quantitative method. The sampling technique in this research used accidental sampling. Distribution of the questionnaire was carried out directly in hardcopy form and also online, namely with the help of Google form. The psychological measurement scale used was a modification of Firin which was adapted by Firdausia (2018). The results of the study showed a high score for gender Stereotype attitudes. This means that there is a strong belief or view regarding the ideal attributes, characteristics, functions, roles, responsibilities, characteristics among men and women that can be accepted by a group of people.